Measuring Quality Change in the Market for Anti-Ulcer Drugs - Haider Rehan; Mehdi Asghar; Zehra Anjum; Kumari Das Geetha; Ahmed Zameer; Zameer Sambreen (Journal of Digestive Disorders And Diagnosis, 2024)
The General Accounting Office released a study in August 1992 of twenty-nine sampled prescription drugs that reported an average increase in the price of approximately 138 percent between 1985 and 1991 (GAO 1992, 4, Table 1) Those and other published price indexes are increasingly being used in the public policy arena to focus the debate on the potential regulation of pharmaceutical prices and the coverage of health insurance. In an industry where products are multidimensional and the rate of technological progress is brisk, misinterpretation of unadjusted indices of drug prices can easily arise. This can lead to erroneous conclusions regarding appropriate policies for the pharmaceutical industry. Researchers have addressed numerous general theoretical issues concerning the construction and interpretation of price indices 1. Two issues of particular interest for pharmaceutical markets are the new goods problem, which deals with the introduction of generic drugs into a drug price index, and the quality problem, which recognizes that newer versions of drugs with the same basic Chemical action may be superior in certain dimensions to drugs already on the market. Specific to pharmaceutical markets, 2 have also argued that the sampling procedure used by the Bureau of Labor Statistics to calculate pharmaceutical price indices is flawed. Each of those problems deserves careful analysis. This study focuses on the issue of product quality measurement and quality change.
Keywords: Efficacy